1975
DOI: 10.1097/00000658-197512000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Staging Laparotomy in the Treatment of Metastatic Melanoma of the Lower Extremities

Abstract: Twenty-six consecutive patients with melanoma of the lower extremities metastatic to the superficial inguinal lymph nodes were subjected to laparotomy. No patient had preoperative evidence of tumor dissemination past the superficial inguinal nodes. However three patients (12%) had metastases to the liver or para-aortic lymph nodes documented at laparotomy and were not subjected to iliac and obturator lymph node dissection. One of these patients had concomitant local recurrence of melanoma at the ankle. The oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Inguino-femoral, external iliac, and obturator nodes must be removed when inguinal nodes are involved. A few years ago, Cohen et al [10] suggested laparotomy as a staging procedure. In 5 patients, they found occult para-aortic lymph node metastases, and in 2 of these patients there were occult liver metastases.…”
Section: Surgery Of Lymph Nodesmentioning
confidence: 99%
“…Inguino-femoral, external iliac, and obturator nodes must be removed when inguinal nodes are involved. A few years ago, Cohen et al [10] suggested laparotomy as a staging procedure. In 5 patients, they found occult para-aortic lymph node metastases, and in 2 of these patients there were occult liver metastases.…”
Section: Surgery Of Lymph Nodesmentioning
confidence: 99%
“…The likelihood then of widespread, disseminated disease is great, and such patients require extensive study by many of the currently available techniques like conventional radiography, radionuclear scans of liver and bone, pulmonary tomography, and gallium scanning. Even if these studies are negative, in a patient with a malignant melanoma on a lower extremity who presents himself with bulky groin metastases, staging by laparotomy is prudent prior to embarking on a surgical procedure that may require both extensive resections to control a primary lesion or a local recurrence and dissection of inguinal‐femoral and iliac‐obturator nodes. As the first step in the treatment of such a patient, laparotomy may be carried out through a lower midline incision to secure biopsy specimens of paraaortic nodes and to palpate the liver for distant spread.…”
Section: Patients Without Palpable Nodesmentioning
confidence: 99%
“…The largest series with the most convincing demonstration of the efficacy of this therapeutic approach is that of Morton et al [94], who demonstrated in 36 patients that 684 of 754 injected nodules regressed completely following intralesional BCG. Cohen et al [99] reported the regression of 119 of 123 BCG-injected nodules in 4 patients. Regression of uninjected nodules occurred in 15-20% of patients.…”
Section: Lmmunotherapy Of Malignant Melanomamentioning
confidence: 99%
“…Nathanson has reported patients having a complete response for more than 19 months [103]. Long-term survivors of greater than 5 years have been reported from the National Cancer Institute [97,99]. Long-term survival of patients following successful intralesional BCG therapy appears to occur only in patients with purely cutaneous metastatic disease.…”
Section: Lmmunotherapy Of Malignant Melanomamentioning
confidence: 99%